Dissonâncias cognitivas regionais no desenvolvimento de uma economia do conhecimento na região oeste do Paraná - Colling, Marcel Augusto (2018)
Behavioral economics has recently been gaining more space in academic studies. The theories based on the rationality of the actors have given place to studies that contemplate their cognitive systems, ways of thinking and emotions. In this context, recent studies in the area of knowledge economy have approached the behavioral framework to analyze the performance and influence of institutions in organizations and vice versa. It occurs that in the relations between different groups in a region, the cognitions of the actors are susceptible to dissonances between beliefs and attitudes. Such imbalances are mitigated by the use of cognitive biases. The influence of these dissonances and biases in the relations between groups in the regional development is the theme addressed in this work. In this perspective, the objective of this dissertation is to analyze the influence and impacts of cognitive dissonance in the relations between the groups of local actors represented by the Government, University and Companies in the Western Region of the State of Parana in view of the knowledge economy. The question that has been sought to answer is how these cognitive processes can represent barriers to a broader understanding by groups about their role in the region in a development context. In order to answer these questions, the present work has proposed to: characterize the Western Region of the State of Parana and the selected municipalities (Cascavel, Toledo, Foz do Iguaçu, Marechal Cândido Rondon, Palotina and Medianeira) according to the relational approaches of the knowledge economy; research the beliefs of local actors representing government, university, and business with a view to the occurrence of cognitive dissonances between beliefs; study the attitudes of each group of local actors regarding the relational aspects addressed by the knowledge economy in terms of cognitive biases and subcategories of dissonance; and explain the reduction or elimination of cognitive dissonance and the use of heuristics and biases in an integrated way by local actors when considering the relations between the different groups. The methodology used was quantitative and qualitative. Initially data were collected regarding Gross Added Value; Number of establishments per activity; Number of jobs per activity; Municipal expenses by function; HDI; Number of public universities; Number of enrollments and graduates in public higher education; Associations formed by groups; Municipal councils. Then, data obtained through questionnaires were analyzed using the methods of Mean Analysis, Pearson Correlations and Stepwise Regression. The next step was the analysis of qualitative data obtained by semi-structured interviews using discourse analysis according to subcategories of cognitive dissonance and cognitive bias. Finally, quantitative and qualitative data were systematically compared according to the subcategories of cognitive dissonance and cognitive bias. The research results showed that, in fact, there are a number of cognitive barriers caused by the heuristics and biases in the three groups. Such barriers prevent them from thinking about innovative ways of institutional action and relational environment so that it hinders the development of the West region of Parana oriented to the knowledge economy.